PENGEMBANGAN MEDIA PEMBELAJARAN ADOBE FLASH CS6 BERBASIS ANDROID PADA MATERI KESETIMBANGAN KIMIA (Kelas XI SMAN 1 Benai) - Ratna Permata Sari; Jumriana Rahayu Ningsih; Dwi Putri Musdansi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
This research on the development of learning media using Android-based Adobe Flash CS6 aims to determine the feasibility of chemistry learning media on equilibrium material for SMA / MA class XI SMAN 1 Benai. This research is a development research (Research and Development, R&D) with the ADDIE development model which includes the Analyze, Design, Development, Implement and Evaluate stages. The research instrument used was the material expert validation sheet, the media expert validation sheet, and the student response validation sheet. The results showed that from the results of the acquisition of material expert validation of 90.33%, media experts by 86.38%, and student response results of 89.19%, based on these results it can be concluded that chemistry learning media using android-based adobe flash CS6 is very suitable for use as a learning medium chemistry in class XI equilibrium material.